Pengaruh Kualitas Pelayanan, Kepercayaan, dan Kualitas Produk terhadap Minat Beli Konsumen Ayam Keprabon - Saputri, Resa Agatha; Anindita, Meisya Laura (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Consumer purchasing interest is influenced by various factors, including service quality, trust, and product quality. Ayam Keprabon as a culinary business actor needs to ensure that these three aspects run optimally. Good service increases satisfaction, trust creates loyalty, and quality products are the main reason consumers buy. All three play an important role in shaping consumer purchasing decisions. By considering these factors, Ayam Keprabon can increase competitiveness and maintain customer loyalty.